PELUANG MEMBANGUN PEREKONOMIAN NASIONAL DENGAN PERBAIKAN SISTEM PEMBIAYAAN BAGI USAHA KECIL DAN MENENGAH (UKM) - Chandra Utama (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Small and medium enterprises (SMEs) have an important role in economy; not only they employ a lot of workers but also contribute to Gross Domestic products (GDP). The SMEs contribute more than 60 percent of GDP (40 percent from small enterprises (SEs)). More than 99 percent of interprises in Indonesia are SMEs and more than 96 percent of worker are employed by them (more than 91 percent work in SEs).Although SMEs are very important for the Indonesian economy, they still have problem to have accessing fund. The SEs invest only 1.5 million rupiahs in average (only 0.0078 and 0.00005 times the average investment of medium (MEs) and big enterprises (BEs) each year) and the MEs invest 855.88 million rupiahs in average (nearly 0.03 times the average investment of BE each year). The data shows that investment for each SE is too small than investment of MEs and BEs. On the other hand the return of investment in SE are more than twice than ME and BE. Although the SMEs contribute 60 percent of total GDP, they only invest 43 percent of total investment every year. The Kredit Usaha Kecil (KUK) that served by commercial Banks for SMEs only contribute 37 percent to total investment of SMEs or 16 percent to total investment. It is proper SMEs invest more than current their investment because they contribute to GDP more than BEs. The intermediation institution (bank) should improve they role in SMEs funding. The development of intermediary system that serve easy funding for SMEs especially SEs is a potential way to increase the economic growth and better distribution of income.